(untitled) (Journal of Scientific Research, 2016)
The present paper deals with possible similarity solution of unsteady boundary layer flow over a vertical plate in the presence of internal heat generation, thermal radiation and buoyancy force. Under suitable similarity transformations, the non-linear partial differential equations are transformed into a set of ordinary differential equations. The transformed ordinary differential equations with boundary conditions are then solved numerically by using sixth order Runge-Kutta integration scheme. The effects of the governing parameters on the flow and thermal fields are investigated and shown graphically for various parameters in the velocity and the temperature distributions. The most essential case is discussed in this paper.